Fundamentals of pervasive information management systems - Kumar, Vijay, 1946- (Hoboken, New Jersey : John Wiley and Sons, Inc., 2013)
"Covering both mobile data and sensor data, this comprehensive text offers updated research on sensor technology, stream data processing, mobile database security, and contextual processing. Packed with exercises and examples, the book covers essential aspects of wireless communication and provides a thorough discussion about managing information on mobile database systems. In addition, the author addresses the integration of web and workflow with mobile computing and looks at the current state of research"--
"Covering both mobile data and sensor data, this comprehensive text offers updated research on sensor technology, stream data processing, mobile database security, and contextual processing"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Management information systems; Mobile communication systems; Mobile computing; COMPUTERS / Computer Engineering; Management information systems; Mobile communication systems; Mobile computing; Electronic books; Electronic books; Electronic books